Features of the endocrine system of female adolescents in cotton-growing regions - Gauri Bapayeva; Saltanat Kulbayeva; Akmaral Zhumadilova (National Scientific Medical Center, 2017)
Objective: to study the features of the endocrine system during the puberty in females living in regions, where organochlorine pesticides are widely used. Materials and Methods:172 females (adolescents aged 10-17) were examined. They were divided into 2 groups, depending on their place of residence. The frst (main) group included 89 females who from birth lived in a territory where organochlorine pesticides were widely used to grow cotton. The second (control) group included 83 females that did not live in such areas. Gonadotropic hormones - follicle stimulating (FSH), luteinizing (LH), prolactin (PL) - and steroid hormones - estradiol (E2), cortisol (K), dehydroepiandrosterone (DHEA) - were examined in all girls. Results: It was found that the levels of FSH and LH in the females of the main group were signifcantly lower (p>0.02) during the whole period of puberty compared to their peers. Thus, the level of FSH at the age of 15-17 years was in the main group - 10.79 ± 0.98 mU / l compared to 16.26 ± 0.21 mU / l, and the level of LH - 10.95 ± 0.66 mU / L and 18.42 ± 1.28 mU / l, respectively. A similar pattern has been established with respect to prolactin at the age of 10-12 years and 13-14 years. Conclusion: the females of the main group have a decreased production of gonadotropic and steroid hormones in the period of the formation of the reproductive system,.